A Primer on Exporting to Honduras - Christina D. Storz; Timothy G. Taylor; Gary F. Fairchild (EDIS, 2005)
Every year the U.S. Department of State publishes extensive Country Commercial Guides for a large number of countries. These guides provide a great deal of information useful to individuals interested in developing export markets either through direct exports or through direct foreign investment. This paper provides an abridged version of the Country Commercial Guide for Honduras as well as supplemental information of direct relevance to agribusiness firms. It is hoped that the information contained in this report provides a useful starting point for individuals interested in exploring export or investment opportunities in Honduras. This is EDIS document FE515, a publication of the Department of Food and Resource Economics, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida, Gainesville, FL. Published February 2005.